The Tadpole of Rhinella azarai (Gallardo, 1965) with Comments on Larval Morphology in the Rhinella granulosa Species Group (Anura: Bufonidae) - Blotto Acuña, Boris Leonardo (2014)
We describe the larval morphology of Rhinella azarai, a medium-sized species of the Rhinella granulosa group. None of the morphological characters allow the larvae of R. azarai to be distinguished unequivocally from those of other species in the group. However, the tadpoles show a distinctive set of character states shared with some species of the group, which may represent putative synapomorphies of the R. granulosa group or internal clades.